Malignant fibrous bag histiocytoma - Croci, Fabio; Real, Julio; Belloso, Rogelio; Calleriza, Fernando (Cirugía del Uruguay, 1986)
Description of a case of malignant fibrous histiocytoma topographied in the scrotum of an aged patient and discussion of this type of sarcoma in soft parts is done.